Clinical course and factors associated with outcomes among 1904 patients hospitalized with COVID-19 in Germany: an observational study. (December 2020) - Nachtigall, Irit; Lenga, Pavlina; Jóźwiak, Katarzyna; Thürmann, Petra; Meier-Hellmann, Andreas; Kuhlen, Ralf; Brederlau, Joerg; Bauer, Torsten; Tebbenjohanns, Juergen; Schwegmann, Karin; Hauptmann, Michael; Dengler, Julius
Abstract: Objectives: In Germany the coronavirus disease 2019 (COVID-19) pandemic situation is unique among large European countries in that incidence and case fatality rate are distinctly lower. We describe the clinical course and examine factors associated with outcomes among patients hospitalized with COVID-19 in Germany. Methods: In this retrospective cohort study we included patients with COVID-19 admitted to a national network of German hospitals between February 12 and June 12, 2020. We examined demographic characteristics, comorbidities and clinical outcomes. Results: We included 1904 patients with a median age of 73 years, 48.5% (924/1904) of whom were female. The mortality rate was 17% (317/1835; 95% confidence interval (95%CI) 16–19), the rate of admission to the intensive care unit (ICU) was 21% (399/1860; 95%CI 20–23), and the rate of invasive mechanical ventilation was 14% (250/1850: 95%CI 12–15). The most prominent risk factors for death were male sex (hazard ratio (HR) 1.45; 95%CI 1.15–1.83), pre-existing lung disease (HR 1.61; 95%CI 1.20–2.16), and increased patient age (HR 4.11 (95%CI 2.57–6.58) for age >79 years versus <60 years). Among patients admitted to the ICU, the mortality rate was 29% (109/374; 95%CI 25–34) and higher in ventilated (33% [77/235; 95%CI 27–39]) than in non-ventilated ICU patients (23%, 32/139; 95%CI 16–30; p < 0.05). Conclusions: In this nationwide series of patients hospitalized with COVID-19 in Germany, in-hospital and ICU mortality rates were substantial. The most prominent risk factors for death were male sex, pre-existing lung disease, and greater patient age.